Dynamic Dust Source Regions and the Associated Natural and Anthropogenic Dust Emissions at the Global Scale - Wang, Zhen; Chen, Siyu; Liu, Chenxi; Chen, Yu; Gong, Yongqi; Cheng, Shanlin (Frontiers in Earth Science, 2022)
Dust emission is a key factor for reproducing dust physical process and its climate impact in dust modeling. However, the previous studies always employed static land cover types to classify potential dust sources, ignoring the dynamic variations in the surface bareness, which may lead to large uncertainties in the simulated dust emission fluxes, especially in regard to anthropogenic dust (AD) emission induced by wind erosion of human-disturbed land surfaces. Combined with anthropogenic land use and land cover change, dynamic dust source regions and the associated natural dust (ND) and AD emissions at the global scale from 2001–2018 are estimated in this study. The results show that the AD emissions exhibit a significant seasonal variability and dispersion at the global scale in contrast to the generally concentrated spatial distributions of ND emissions. The high-value ND areas are primarily located in Sahara Desert, the Arabian Peninsula, Karakum Desert, East Asia, Australian Desert and other large desert areas, and the ND emission flux reaches a maximum of 50 μg m-2 s-1 or higher. High values of the annual average AD emission fluxes are located in the southern Russia (124.6±26.6 μg m-2 s-1), the northern China (103.2±21.9 μg m-2 s-1), the central and northern USA (56.0±17.4 μg m-2 s-1) and the southern side of the Sahara Desert (74.1±14.2 μg m-2 s-1). Especially in the southern Russia and the northern Kazakhstan, the AD emission flux accounts for the largest contribution to the total dust emission flux, at 98.2%. The ND emission flux demonstrates an upward trend in the central Sahara Desert, southern Arabian Desert and Iranian regions and a significant downward trend in the northwestern China. The AD emissions exhibit a decreasing trend in the northern China, the western India, the southern side of the Sahara Desert and central United States from 2001–2018 due to the implementation of environmental protection policies and a decrease in the wind speed, with the highest rate of decline, reaching -74.9 μg m-2 s-1/decade. This study provided confidence for the further investigation of dust mass balance and the climatic impacts of natural and anthropogenic dust.